Implementasi Pendidikan Karakter Berbasis Nilai-nilai Sosio-kultural di Madrasah Aliyah - Rohman, Miftahur; Nabilla, Nabilla; Frimayanti, Ade Imelda (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study is based on the importance of implementing character education values ​​in madrasas, which in fact are educational institutions under the auspices of Islamic boarding schools. MA Bustanul 'Ulum under the auspices of the Bustanul 'Ulum Development Islamic Boarding School Education Foundation (YPPPBU) Central Lampung is one of the Islamic educational institutions that has long implemented character education. This qualitative research aims to determine and analyze character education management using a socio-cultural values ​​approach at MA Bustanul 'Ulum Jayasakti, Central Lampung. This research uses a qualitative research approach by taking research informants from foundation leaders, madrasa leaders, and five teachers' councils. Through in-depth interview techniques, observation, and documentation, data was collected from informants which was then analyzed through the stages of data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, researchers used data triangulation. In the end, this research found the fact that the internalization of character education values ​​at MA Bustanul 'Ulum was carried out through a planning, implementation and evaluation process with certain steps. The planning involved the entire madrasah and Islamic boarding school management team, considering that this madrasah is a madrasah within the scope of Islamic boarding schools. With careful planning and determining the person in charge of the education program, the implementation of character education is carried out well through intracurricular and extracurricular learning activities that are integrated with Islamic boarding schools. The research results have implications for the importance of strengthening digital literacy in order to strengthen the values ​​of character education.